Confucius, Rawls, and the sense of justice - Cline, Erin M. (New York : Fordham University Press, 2013)
This text compares the role of a sense of justice in the ethical and political thought of Confucius and John Rawls. The author demonstrates that the Analects and Rawls's work intersect in an emphasis of the importance of developing a sense of justice.
Methods in comparative work -- The sense of justice in Rawls -- The sense of justice in the Analects -- Two senses of justice -- The contemporary relevance of a sense of justice.
Includes bibliographical references (pages 273-349) and index.
English.
JSTOR
Keywords: Confucius; Rawls, John, -- 1921-2002.; Confucius; Confucius; Rawls, John, -- 1921-2002; Justice (Philosophy); Justice (Philosophie); PHILOSOPHY -- General; Justice (Philosophy)